The association between connectedness towards religion, family, and school, and the symptoms of depression, anxiety, and stress among Malaysian adolescents / Siti Sabariah Samian - Siti Sabariah, Samian (2020)
The unmet alignment between reality and expectation in addition to immaturity in the development of the prefrontal area means adolescents have tendencies to embark on poor decisions, making them vulnerable to acquiring mental health problems. Abiding by their religion and strong connections with family and school has been proven in European/Western nations to promote adolescent mental well-being, provide ventilation to release stress and protect the youngsters from acquiring anxiety and depression. Given the vast differences between European/Western social norms and Eastern culture, this study was conducted to examine the association between adolescent connectedness towards religion, family and school on the symptom of depression, anxiety and stress in the Malaysian context which is a multiracial country. The study was conducted in two phases. The first phase of the study was performed to test and retest the reliability of the bilingual BM/English Version of The Hemingway Measure of Adolescent Connectedness which involved 338 students of Form 1, Form 2 and Form 4 of three secondary schools in Kuala Langat, Selangor. The second phase was a cross-sectional study with participants comprising adolescents attending Form 1, Form 2 and Form 4 from 16 government secondary schools in Selangor, Malaysia but excluding three schools that had participated in test and retest reliability study. The data collection period was from 1st May 2019 till 30th September 2019. The Hemingway Measure of Adolescent Connectedness was utilised to assess adolescent connectedness towards religion, family and school, and the DASS-21 was employed to elicit symptoms of stress, anxiety and depression. Multiple Linear Regression Analyses were employed to determine the association. iv The score of adolescent connectedness towards school was associated with lower score of symptoms of depression, anxiety and stress (depression: β = -2.24, p < 0.0001; anxiety: β = -1.29, p < 0.0001; stress: β = -1.93, p < 0.0001). In contrast, connectedness towards teacher showed higher score of symptoms of stress (β = 0.85, p = 0.002). Concerning family, one unit increment in the score of connectedness towards father was associated with reduction of the symptoms of depression, anxiety and stress by 1.76, 1.26 and 1.54, respectively (depression: β = -1.76, p < 0.0001; anxiety: β = -1.26, p < 0.0001; stress: β = -1.54, p < 0.0001). Whereas, connectedness towards mother showed no significant association for the scores related to stress, anxiety and depression (depression: β = -0.60, p = 0.06; anxiety: β = -0.23, p = 0.48; stress: β = -0.20, p= 0.56). Being connected to their siblings was associated with lesser symptom of depression symptom (β = -0.96, p < 0.0001). However, adolescent connectedness toward religion showed positive association on the score of anxiety and stress symptoms (anxiety: β = 0.64, p < 0.0001; stress: β = 0.50, p= 0.01). Since temporal relationship could not be excluded, hence a longitudinal study was suggested for future investigation. This study showed that the provision of a safe and caring school environment and the father’s contribution in adolescent life would have a strong protective effect in preventing adolescents from acquiring mental health problems. Keywords: Adolescent, Religion, Family, School, Mental Health